Multiplicação de colônias de uma nova espécie de Scaptotrigona: produção de rainhas in vitro e técnicas de divisão - Rocha, Epifânia Emanuela de Macêdo (2018)
This work aims to study and develop techniques for the creation, management and 135 multiplication of Scaptotrigona sp. nov. The study was carried out at the Bees Sector of the 136 Federal University of Ceará, from February 2014 to November 2016. For the preparation and 137 formation of the new colonies, two methods were used: I) Introduction of cells or Virgin Queens 138 (VQs) in the daughter colonies (traditional model) and II) introduction of cells or VQs in mini 139 colonies. In all, 52 attempts to form new colonies were made and the analyzes showed that there 140 was no difference between the methods (p = 0.771) used, nor between years (p = 0.307), but 141 there was an influence of the rainfall of the period (p = 0.046) about the success of the method. 142 As for the emergence of the queen, the analysis showed that there was no influence of 143 precipitation (p = 0.235), nor was there a difference between methods (p = 0.788) used, but 144 there was a difference between years (p = 0.025). The analysis on the beginning of the laying 145 showed that there was no influence of rainfall (p = 0.449), nor years (p = 0.148), but there was 146 a difference between methods (p = 0.002). In this study, rainfall has negatively influenced the 147 success of the method used to form new colonies. Queens installed in mini colonies were 148 quicker to start laying activity. For the in vitro production of queens and their acceptance in 149 new colonies, the critical period was in relation to the number of surviving pupae, as there was 150 more loss in the larva to pupa phase (34%) in relation to the pupa to queen phase (24%), with 151 a 49% difference in success from the larval to pupal stage between the tests. On average, the 152 virgin queens' stay in the colonies after their introduction was 5.61 (± 4.02). The acceptance 153 rates of the introduced queens were separated into three age groups on days 0 to 4 (77%), 5 to 154 9 (82%) and 10 to 14 (100%). There was no relationship (p> 0.05) between the ages of 155 introduction of virgin queens and the acceptance rate. Although the study showed a good 156 acceptance rate (80%.), We were unable to evaluate the establishment of new colonies in 157 Scaptotrigona sp. nov., because none of the queens that left for flight returned to the colony.